Hoarding Disorder in Islamic Religious Education: Reconstructing Human–Object Relations Based on Islamic Values - Adnan Syah Sitorus; Eva Latipah (Indonesian Journal of Action Research, 2026)
Purpose – This study aims to examine the phenomenon of hoarding disorder as a form of imbalance in the relationship between humans and objects, analyze relevant Islamic values in shaping attitudes toward material possessions, and formulate a conceptual model within Islamic Religious Education that can reconstruct the human–object relationship in a more proportional manner. Design/methods– This study employs a qualitative approach using an interdisciplinary conceptual synthesis design, integrating literature from the fields of psychology, Islamic ethics, and education. Analysis was conducted through the stages of conceptual mapping, comparative analysis, integrative synthesis, and model construction.   Findings – The research findings indicate that hoarding disorder can be understood as a dysfunction in the construction of values regarding objects, which is associated with cognitive distortions and excessive emotional attachment. Based on these findings, this study proposes the Model of Reconstruction of Human–Object Relationships Based on Islamic Values, comprising three main dimensions: value reorientation, cognitive restructuring, and attachment regulation. This model serves as a conceptual framework in Islamic Religious Education to foster rational, proportional, and utility-oriented attitudes toward objects. The contribution of this study lies in the integration of psychological approaches and Islamic values within an educational context, as well as in the development of a conceptual model that can be utilized as a preventive approach in addressing the phenomenon of hoarding disorder.